2004
DOI: 10.1097/00129492-200407000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pachymeningitis Presenting as Asymmetric Sensorineural Hearing Loss

Abstract: The clinician should be aware that the evaluation of a patient with asymmetric sensorineural hearing loss involves more than simply ruling out an acoustic neuroma. Fast-spin echo MRI techniques without the use of gadolinium contrast could miss a number of potentially treatable diseases such as chronic pachymeningitis. Patients with asymmetric sensorineural hearing loss should be carefully evaluated for other neurologic findings, and imaging with enhanced MRI is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Nonneoplastic causes of asymmetric SNHL may include labyrinthitis, chronic pachymeningitis, intralabyrinthine hemorrhage, and otospongiosis. In a retrospective study on 3,000 patients with asymmetric SNHL, 3 were found to have chronic pachymeningitis based on MRI, either linear or hypertrophic T1 enhancement of the pachymeninges (dura mater) as opposed to the leptomeninges (pia and arachnoid mater); this is what is typically enhanced in neurosarcoidosis [Oghalai et al, 2004]. The 2 pathologies are not distinct, as chronic pachymeningitis may be caused by viral, bacterial, or fungal meningitis, parasitic and other infections, malignancy, idiopathic etiology, or autoimmune diseases including neurosarcoidosis [Oghalai et al, 2004].…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Nonneoplastic causes of asymmetric SNHL may include labyrinthitis, chronic pachymeningitis, intralabyrinthine hemorrhage, and otospongiosis. In a retrospective study on 3,000 patients with asymmetric SNHL, 3 were found to have chronic pachymeningitis based on MRI, either linear or hypertrophic T1 enhancement of the pachymeninges (dura mater) as opposed to the leptomeninges (pia and arachnoid mater); this is what is typically enhanced in neurosarcoidosis [Oghalai et al, 2004]. The 2 pathologies are not distinct, as chronic pachymeningitis may be caused by viral, bacterial, or fungal meningitis, parasitic and other infections, malignancy, idiopathic etiology, or autoimmune diseases including neurosarcoidosis [Oghalai et al, 2004].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In a retrospective study on 3,000 patients with asymmetric SNHL, 3 were found to have chronic pachymeningitis based on MRI, either linear or hypertrophic T1 enhancement of the pachymeninges (dura mater) as opposed to the leptomeninges (pia and arachnoid mater); this is what is typically enhanced in neurosarcoidosis [Oghalai et al, 2004]. The 2 pathologies are not distinct, as chronic pachymeningitis may be caused by viral, bacterial, or fungal meningitis, parasitic and other infections, malignancy, idiopathic etiology, or autoimmune diseases including neurosarcoidosis [Oghalai et al, 2004]. In 1 study, idiopathic chronic pachymeningitis causing bilateral SNHL and facial weakness was only distinguished from neurosarcoidosis once a dural biopsy had been performed and found negative for granulomas [Christakis et al, 2012].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The case we reviewed is peculiar for the bilateral and almost symmetrical hearing and vestibular loss, that is in contrast with monolateral or asymmetrical cases previously reported in literature (Oghalai et al, 2004;Iwasaki et al, 2003). Furthermore, the typically slow progressive clinical manifestation of HP was even more insidious as a consequence of the repeated steroid treatments that were given before the correct diagnosis was made.…”
Section: Discussionmentioning
confidence: 82%
“…50 Although noncontrast MRI may detect features of dural inflammation, gadolinium is required to assure proper diagnosis of the described patterns. 51 Corticosteroids are the treatment of choice.…”
Section: Other Inflammatory Lesionsmentioning
confidence: 99%